SANS study of liquid crystal doped with CoFe2O4 nanoparticles - Zakutanská, Katarína; Feoktystov, A.; Lacková, V.; Tomašovičová, N.; Appel, Ingo; Behrens, Silke; Kopčanský, P. (Acta physica Polonica, 2020)
In the present paper, small-angle neutron scattering results from measurements performed on 4-n-pentyl-4'- cyanobiphenyl liquid crystal and magnetic spherical cobalt ferrite CoFe2O4 nanoparticles suspension are presented. To prevent aggregation, the nanoparticles were coated with mesogenic ligands. Samples with two nanoparticle concentrations of 0.0854 wt% and 0.0623 wt% as well as pure liquid crystal were investigated. Measurements in zero magnetic field and in magnetic field up to 2.2 T were carried out. The samples were oriented in the cells in zero magnetic field and aligned when large enough magnetic field was applied. Moreover, the results showed a presence of elongated objects in the samples.
Im Titel sind die Zahlen "2" und "4" tiefgestellt
Proceedings of the 17th Czech and Slovak Conference on Magnetism, Košice, Slovakia, June 3-7, 20
Gesehen am 30.09.2020